132k views
3 votes
Show that:


\bigg(( √(7) + i √(3) )/(√(7) - i √(3) ) + {( √(7) - i √(3) )/( √(7) + i √(3) ) } \bigg) \: is \: real \\
Please answer this question.​

User Peter Zhao
by
4.9k points

1 Answer

2 votes

Explanation:


\large\underline{\sf{Solution-}}

Consider,


\rm \longmapsto\:( √(7) + i √(3) )/( √(7) - i √(3)) + ( √(7) - i √(3) )/( √(7) + i √(3) )

On taking LCM, we get


\rm \:  =  \: \frac{ {( √(7) + i √(3))}^(2) + {( √(7) - i √(3))}^(2) }{( √(7) + i √(3))( √(7) - i √(3))}

We know,


\purple{\rm \longmapsto\:\boxed{\tt{ {(x + y)}^(2) + {(x - y)}^(2) = 2( {x}^(2) + {y}^(2))}}} \\

and


\purple{\rm \longmapsto\:\boxed{\tt{ (x + y)(x - y) = {x}^(2) - {y}^(2) \: }}} \\

So, using these Identities, we get


\rm \:  =  \: \frac{2\bigg[ {( √(7))}^(2) + {(i √(3)) }^(2) \bigg]}{ {( √(7)) }^(2) - {(i √(3))}^(2) }


\rm \:  =  \: \frac{2(7 + 3 {i}^(2))}{7 - {3i}^(2) }

We know,


\purple{\rm \longmapsto\:\boxed{\tt{ {i}^(2) = - 1}}} \\

So, using this, we get


\rm \:  =  \: (2(7 - 3))/(7 + 3)


\rm \:  =  \: (2 * 4)/(10)


\rm \:  =  \: (4)/(5)

Hence,


\red{\rm\implies \:\boxed{\sf{ ( √(7) + i √(3) )/( √(7) - i √(3)) + ( √(7) - i √(3) )/( √(7) + i √(3) ) \: is \: purely \: real}}}

User Elora
by
4.2k points